The Relationship between Food Production, Agricultural Land, Rice Production, and Rice Price: An Empirical Study on Thailand and Viet Nam - Nguyen, Anh Tru (International Journal of Sustainable Agricultural Research, 2020)
Food security has been considered as one of priorities in the development of socio-economics of Southeast Asian countries. The article aims to examine the causal relationship between food production, agricultural land, rice production and rice price in Thailand and Viet Nam between 1988 and 2017. We found that agricultural land positively affects food production index. We also found that paddy rice production has a positive relationship with food production index. Results showed that there are directional relationships running from food production index to agricultural land and paddy rice production; from agricultural land to paddy rice production; from paddy rice production to food production index; and from rice price to agricultural land. Further, there is a co-integration among variables in the long run. Lastly, policies are recommended to ensure food security and achieve a sustainable development in Thailand and Viet Nam.